Seizing the square 1989pProtests in China and Germany from a global perspective - Palm, Daniel (SpatioTemporality, 2020)
Frontmatter -- Contents -- Introduction -- I. On the SpaceTime of 1989 -- II. Towards the Global Moment of 1989 -- III. The Global Moment of 1989 in Leipzig and Beijing -- IV. Producing Counter-spaces on the Squares in 1989 -- Lessons from 1989 for 2011 and after -- Acknowledgements -- Bibliography -- List of abbreviations -- Index